Ionospheric quasi-biennial oscillation of the TEC amplitude of the equatorial ionization anomaly crests from continuous GPS data in the Southeast Asian region - Nguyen Thanh, Dung; Le Huy, Minh; Amory-Mazaudier, Christine; Fleury, Rolland; Saito, Susumu; Nguyen Chien, Thang; Le Truong, Thanh; Pham Thi Thu, Hong; Nguyen Ha, Thanh; Nguyen Thi, Mai; et al. (Vietnam Journal of Earth Sciences, 2022)
The quasi-biennial oscillation (QBO) signals at two Equatorial ionization anomaly (EIA) crests of the ionosphere have been studied using the continuous GNSS network data in Vietnam and adjacent regions during the 2008- 2021 period. The monthly mean EIA crests amplitudes are calculated. The Lomb-Scargle periodogram method was applied to the residuals of the EIA crests magnitudes, ΔTEC, which are obtained from subtracting the fittings with solar index, F10.7. The Lomb-Scargle spectrum shows the quasi-biennial component in the residuals ΔTEC with the picks at 18, 25, and 29-30 months. The ionosphere QBO at two EIA crests was found out by the band-pass filter centered at 25 months with haft-power points at 17 and 33 months. The zonal wind data at 50 hPa ( 20 km) of the tropical equatorial stratosphere is used as the stratosphere QBO (SQBO) to consider the relationship between the SQBO and the obtained ionosphere QBO. The direct comparison and the cross wavelet transform of the SQBO and ionosphere QBO data series show that during 2008-2009, the ionosphere QBO signal is low, the SQBO and ionosphere QBO are in phase during the 2010-2013 and 2018-2021 periods, but anti-phase during the 2014-2017 period. For the 2010-2013, 2014-2017 and 2018-2021 periods, the correlation coefficients are 0.623, 0.637, -0.646 in the northern crest, and 0.571, 0.53, -0.530 in the southern crest, respectively. Furthermore, we also observed that the SQBO and the ionosphere QBO signals were shortened during the 2015-2016 period, approximately 1.5 years. Previous studies showed that the ENSO (El Niño - Southern Oscillation) warm phase, also known as El-Niño existed during 2015-2016. The results of this study allow us to assume that the SQBO influences the ionosphere QBO. Our results show that the SQBO is the main factor affecting the ionospheric QBO at two EIA crests. However, the physical theoretical interpretation of the mechanisms of action is a challenge for scientists and requires further research.